Methanol extract of Dicranopteris linearis leaves attenuate pain via the modulation of opioid/NO-mediated pathway - Zakaria, Zainul Amiruddin; Roosli, Rushduddin Al Jufri; Marmaya, Najihah Hanisah; Omar, Maizatul Hasyima; Basir, Rusliza; Somchit, Muhammad Nazrul (MDPI, 2020)
Dicranopteris linearis leaf has been reported to exert antinociceptive activity. The present study elucidates the possible mechanisms of antinociception modulated by the methanol extract of D. linearis leaves (MEDL) using various mouse models. The extract (25, 150, and 300 mg/kg) was administered orally to mice for 30 min priot to subjection to the acetic acid-induced writhing-, hot plate- or formalin-test to establish the antinociceptive profile of MEDL. The most effective dose was then used in the elucidation of possible mechanisms of action stage. The extract was also subjected to the phytochemical analyses. The results confirmed that MEDL exerted significant (p < 0.05) antinociceptive activity in those pain models as well as the capsaicin-, glutamate-, bradykinin- and phorbol 12-myristate 13-acetate (PMA)-induced paw licking model. Pretreatment with naloxone (a non-selective opioid antagonist) significantly (p < 0.05) reversed MEDL effect on thermal nociception. Only l-arginine (a nitric oxide (NO) donor) but not N(ω)-nitro-l-arginine methyl ester (l-NAME; a NO inhibitor) or 1H-[1,2,4]oxadiazolo[4,3-a]quinoxalin-1-one (ODQ; a specific soluble guanylyl cyclase inhibitor) significantly (p < 0.05) modified MEDL effect on the writhing test. Several polyphenolics and volatile antinociceptive compounds were detected in MEDL. In conclusion, MEDL exerted the opioid/NO-mediated antinociceptive activity, thus, justify D. linearis as a potential source for new analgesic agents development.